Kemandirian Petani Padi dalam Pengendalian Hama Terpadu di Kecamatan Bendosari Kabupaten Sukoharjo - Pekerti, Ratih Dewi (Journal of Integrated Agricultural Socio-Economics and Entrepreneurial Research (JIASEE), 2023)
Rice farmers in Bendosari district have been educated with the integrated pest management program. However, farmers are not implementing an integrated pest management approach based on IPM principles. So far, the application of pesticides is measured roughly, the lack of utilization of natural enemies, the lack of routine observations, and the decision-making based on other farmer. Related to these problems, farmer self-reliance is needed in integrated pest management to increase productivity. This study aims to examine the self-reliance of rice farmers in integrated pest management, examine the factors forming the self-reliance of rice farmers in integrated pest management, and examine the influence of the factors forming self-reliance on the self-reliance of rice farmers in integrated pest management in Bendosari District, Sukoharjo Regency. The primary research method is quantitative. Sampling method using a quota sampling consisting of 64 respondents. Data was analyzed by multiple linear analyses with the IBM SPSS Statistics 25 program. The results showed that there was a significant influence of the forming factors of self-reliance on the rice farmers’s self-reliance in integrated pest management. Influential factors such as the area of farming land, farming experience, the role of agricultural extension, and the role of farmer groups.